Student preferences, expectations and anxieties regarding an online exchange program: reports from Japan and Vietnam - Guest, Michael; Duyen, Le Thi Hong (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
Online cultural exchanges between students of different nationalities may be quite common in this digital age but expanding and adjusting them to include new and more specialized participants can be a challenging task. The Online Cultural Exchange Program (OCEP), currently hosted by the University of Miyazaki (Japan) has been functioning successfully since 2007 (see Araki, Shirasaka, and Larson, 2008), gradually expanding its scope from nursing students alone to include engineering and agriculture majors, consisting largely of online written personal introductions and light-hearted cultural exchanges. However, recent planned expansions of the program into the Faculty of Medicine between the host university in Japan and a new participant in Vietnam has demanded a re-evaluation of what is expected from the program with regard to its utility for medical students. In order to develop a focus suited to the academic and professional needs of medical students in both the hosting university (Miyazaki, Japan) and the new Vietnamese participant (Haiphong University of Medicine and Pharmacy) a pre-program survey was designed by the authors in order to gauge medical students’ expectations, specific interests, preferences, anxieties, and abilities to fruitfully participate in such a program. In this paper, some salient results of these surveys are presented, along with the implications of moving the program towards a more professional and academic focus, and cultural factors that may affect participant expectations and potential outcomes. We expect that the data generated from these surveys may inform and influence similar international online exchange and learning programs being established elsewhere.